Perspectives in cultural differences and conflicts between Finnish and Asian partners in intercultural marriages - Ha, Anh (2020)
In this study, the topic of conflict communication in intercultural marriages, marital satisfaction, and third culture building is examined. Even though intercultural couples are identified to have stronger bonds, a unique sense of identity and reduced ethnocentricity, communication dysfunction, stress, and conflicts are still considered the most negative factors in a romantic relationship. This study aims to bring the topic of conflict communication in intercultural marriages into clear view. It includes three research questions: (1) How do people living in intercultural marriages describe the role of culture(s) in encountering conflicts?, (2) How do intercultural marital couples describe the communication strategies they implement in managing conflicts?, and (3) How do intercultural marital couples describe the role of third cultures (building) for their relationship?. To collect the data for analysis, six (6) participants, making up three (3) couples, were interviewed separately about their conflict communication and reconciliation strategies. The theory of Third Culture Building was utilized to investigate how Third Culture Building influences intercultural romantic relationships and has an impact on reconciling marital conflicts. The findings from this research highlight the role of practical help, open communication, empathy, patience and gratitude in reconciling intercultural couples’ marital conflicts.